Genomic knockout of hsp23 both decreases and increases fitness under opposing thermal extremes in Drosophila melanogaster. (December 2021) - Gu, Xinyue; Chen, Wei; Perry, Trent; Batterham, Philip; Hoffmann, Ary A.
Abstract: Under exposure to harmful environmental stresses, organisms exhibit a general stress response involving upregulation of the expression of heat shock proteins (HSPs) which is thought to be adaptive. Small heat shock proteins (sHSPs) are key components of this response, although shsp genes may have other essential roles in development. However, the upregulation of expression of a suite of genes under stress may not necessarily be evidence of an adaptive response to stress that involves those genes. To explore this issue, we used the CRISPR/Cas9 system to investigate pleiotropic effects of the hsp23 gene in Drosophila melanogaster . Transgenic flies carrying a pCFD5 plasmid containing sgRNAs were created to generate a complete knockout of the hsp23 gene. The transgenic line lacking hsp23 showed an increased hatch rate and no major fitness costs under an intermediate temperature used for culturing the flies. In addition, hsp23 knockout affected tolerance to hot and cold temperature extremes but in opposing directions; knockout flies had reduced tolerance to cold, but increased tolerance to heat. Despite this, hsp23 expression (in wild type flies) was increased under both hot and cold conditions. The hsp23 gene was required for heat hardening at the pupal stage, but not at the 1st-instar larval stage, even though the gene was upregulated in wild type controls at that life stage. The phenotypic effects of hsp23 were not compensated for by expression changes in other shsp s . Our study shows that the fitness consequences of an hsp gene knockout depends on environmental conditions, with potential fitness benefits of gene loss even under conditions when the gene is normally upregulated. Graphical abstract: Image 1 Highlights: CRISPR/Cas9 was used to generate complete hsp23 knockout in Drosophila melanogaster. The fitness of hsp23 knockout flies depends on environmental conditions, with fitness benefits of gene loss. The hsp23 knockout affected heat and cold tolerance in opposing directions . The hsp23 gene was required for heat hardening at the pupal stage but not at the 1st-instar larval stage. The study highlights the challenges of undertaking gene-based assessments when assessing adaptive plasticity hypotheses.